Social coordination problems in classical and Marxian political economy. Issue 1 (2nd January 2020) - Foley, Duncan
Abstract : This paper explores the application of information theory and game theory to questions arising in Adam Smith's Wealth of Nations and Karl Marx's critical reformulation of Smith's analysis in Capital . After introducing the key theoretical concepts of entropy-constrained behavior and the social interaction model, the paper applies them to some central issues in Marxian and classical political economy: the long-period method analysis of commodity production, the social division of labor, commodity production and money, alienation, and the tendency for the rate of profit to fall.